Blater VS Kyai: The Dynamics of Dualism in The 2024 Sampang Regional Election Contest - Sohibul Amin; Syi'a'ur Rofiqi (Journal of Religion, Local Politics, and Law, 2025)
The 2024 Sampang Regional Election is an arena for political contestation that is able to bring together two great powers in traditional Madura society, namely Blater and Kyai. Blater is someone who represents a traditional power based on local social and cultural influences. When dealing directly with a Kyai, he becomes a symbol of religious authority that has spiritual legitimacy among religious people, especially students. This study aims to analyze the dynamics of competition between these two forces in fighting for political support, as well as their impact on voter patterns, social stability, and the ongoing democratic process in Sampang today. Using a qualitative approach, this study explores the political strategy, narrative built, and alliance formed between Blater and Kyai. In addition, this study also examines how the power of this dualism is able to influence people's perception of local leadership patterns and how they use cultural and religious symbols to strengthen their respective political positions. The results of this study are expected to provide in-depth insights into the interaction between traditional and religious forces in the local political context, as well as the implications of democracy at the regional level